PERSEPSI GURU RAUDHATUL ATHFAL TERHADAP PERKEMBANGAN MORAL GENERASI ALPHA USIA DINI - Atika Mentari Nataya Nasution; Cut Sarah (Jurnal Genta Mulia, 2025)
This research aims to determine the description of teachers' perceptions of the moral development of the early age alpha generation. Raudhatul Anfal (RA) teachers are the focus of the researcher, they are teachers at the Kindergarten (TP) level with an emphasis on an Islamic-based curriculum. The research method used is a qualitative method with a phenomenological type to describe, explore and deepen understanding of the phenomenon. The sampling technique was through purposive sampling with the criteria of teachers who have taught for at least 1 year with a total of 6 participants at RA Al-Barkah, Jalan Puskesmas, Kelurahan Tanjung Gusta, Medan City. The results of the study found that in general RA Al-Barkah teachers have a positive perception of the moral development of the early age alpha generation who are their students. This is illustrated through four themes regarding the moral development of early childhood, namely honest behavior, polite and respectful behavior, helpful and tolerant behavior, and obedient behavior.